Managing BTSs to Solve Handover Problem in Mobile Network - Etaiwi, Wael; Almhairat, Haitham; Jarad, Mujahed; Batarseh, Laith (International Journal of Interactive Mobile Technologies (iJIM), 2010)
Handover is a key solution that improves the telecommunication services using GSM by assure the continual service delivery between two mobiles regardless of location’s changes of the sender or receiver, and now GSM technology becomes applicable all over the world and the customers become more satisfied to the dealer’s services delivery, But Handover suffers from a major problem refers to the limitation of hardware capacity of the BTS (Base Transfer Station). This approach consists of three schemes, the first one based on reserve an extra ports for handover purposes by implementing a software solution that control BTS ports. The second alternative scheme based on channel exchange between adjacent BTSs by shifting a chosen allocated signal to another adjacent free BTS and then allocating the new signal to the new free port. The third schema depends on carrying the Handover problem to another BTS to solve it if it didn’t solved in the second schema.